2020
DOI: 10.1021/acs.jpcb.0c08624
|View full text |Cite
|
Sign up to set email alerts
|

Combined Computational and Experimental Investigation on the Nature of Hydrated Iodoplumbate Complexes: Insights into the Dual Role of Water in Perovskite Precursor Solutions

Abstract: Water is generally considered an enemy of metal halide perovskites, being responsible for their rapid degradation and, consequently, undermining the long-term stability of perovskite-based solar cells. However, beneficial effects of liquid water have been surprisingly observed, and synthetic routes including water treatments have shown to improve the quality of perovskite films. This suggests that the interactions of water with perovskites and their precursors are far from being completely understood, as water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 96 publications
0
34
0
Order By: Relevance
“…The nature of the organic cation but, also, the strength of the bond between the central bivalent cation and the halide, have therefore a huge impact on these degradation path. Logically hydrophobic cations could protect the structure from the water entrance and strong metal halide bonds could offer superior resistance to the attack [52].…”
Section: Pb-free Perovskites For H 2 Evolutionmentioning
confidence: 99%
“…The nature of the organic cation but, also, the strength of the bond between the central bivalent cation and the halide, have therefore a huge impact on these degradation path. Logically hydrophobic cations could protect the structure from the water entrance and strong metal halide bonds could offer superior resistance to the attack [52].…”
Section: Pb-free Perovskites For H 2 Evolutionmentioning
confidence: 99%
“…The ability of in silico experiments to decouple the various effects in play has been exploited to interpret experimental data on the formation and the optical response of these systems. [21,[37][38][39][40] In addition, high-throughput screening has been proven as a reliable and cost-effective method to explore large configurational spaces in view of the synthesis and characterization of these complex materials. [21,41] Motivated by these successful contributions from theory, in this work, we want to further explore the formation of LHP solution precursors adopting a physicists' perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the chemical complexity of the precursor solution, the presence of oxygen and moisture in ambient air results in an uncertainty of the precursor recipe developed for the glovebox process to be transferred to the ambient process. Water molecules attack the perovskite film by forming the (CH 3 NH 3 ) 4 PbI 6 di-hydrated phase and PbI 2 via the chemical reaction (Radicchi et al, 2020)…”
Section: Development Of Ambient Air-processed Pscs-toward Manufacturementioning
confidence: 99%
“…The release of two water molecules provides the self-sustainability of the chemical reaction process, resulting in the degradation of the complete perovskite film. Computational studies also showed that aqueous solutions inhabited the formation process of perovskites, but small amount of water could be added as an additive for the deposition of perovskite materials (Radicchi et al, 2020). A study has been conducted recently to provide a comprehensive understanding of the improvement of PSC stability against water molecules through compositional engineering (Li et al, 2021).…”
Section: (Ch 3 Nhmentioning
confidence: 99%